Development of RP-HPLC method for simultaneous estimation of ezetimibe and simvastatin in tablet formulation - Esmail O. Elakesh (International Journal of Pharmacy and Analytical Research, 2015)
A new, accurate, precise and robust HPLC method was developed and validated for the determination of Ezetimibe and Simvastatin in tablet dosage form. The chromatographic separation was achieved on an X-Terra C18 (150mm x 4.6mm, 3.5 µm) stationary phase maintained at ambient temperature with a mobile phase combination of 0.1% TEA and Acetonitrile (30:70) at a flow rate of 1.4 mL/min, and the detection was carried out by using UV detector at 238 nm. The total run time was 8 min. The retention time of Ezetimibe and Simvastatin were found to be 1.721 min. and 4.618 min. respectively. The performance of the method was validated according to the present ICH guidelines.